A Study to Assess Level of Satisfaction Regarding Health Services Provided Through Selected Urban Health Centre among People Residing in Urban Slums - Dr.Suresh Ray, Archana Kane, Liya Yohannan, Merlin B Mathew, Aniket Suryawanshi, Ms.Kiran jagdale (Drugs and Cell Therapies in Hematology, 2021)
Health care includes Preventive, Promotive, curative and rehabilitative services to the people. Health care provided by Urban Health care Canters and the outcome of care are the important factors for the outcome of the health related issues among urban slum dwellers. The current study was conducted to assess the level of satisfaction towards health services provided through urban health centres. Methodology: In this study quantitative research approach & descriptive research design was used. 100 adults were selected as samples with age group of 20-44years. Samples of were selected through non purposive sampling technique. Self structured questionnaire was prepared having 35 items to collect the responses from the samples. Result: Majority (63%+35%) were satisfied with the services provided through urban health centre. Conclusion: Current research study has explored the level of satisfaction in different areas of services provided through urban health centre which includes the infrastructure and health care workers also. Findings of the current study will make the health care workers more motivated towards their work and also the administrative authority to continue the services on the same scale.